The effectiveness of active recovery (jogging and cycling) post-football match simulation on athletes' heart rate and fatigue levels - Akbar, Muhammad; Dwi Marhaendro, Agus Susworo; Dharma Hita, I Putu Agus; Ariestika, Elsa (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2021)
Active recovery is recommended to help the soccer player recover quickly. However, there has been no study comparing the most effective active recovery methods post-match. The purpose of this study was to compare active recovery (jogging and cycling) to the heart rate and fatigue level of athletes. This study uses an experimental method with a pretest-posttest crossover design approach. Subjects were 22 male amateur football athletes with an average (age, 19.40 ± 1.18 years; height, 170.04 ± 3.54 cm; weight, 62.89 ± 5.44 kg). The results showed that the average heart rate (HR), vertical jump (VJ), and lactate levels between groups after the simulation match did not show significant differences (HR p= 0.748, VJ p=0.984, lactate p=0.633). However, for variables HR and lactate levels experienced a significant decrease after undergoing recovery treatment, and when viewed from the delta the jogging group experienced a decrease (HR 24.7%, and lactate 52.5%), for the bicycle group (HR 29.3%, and lactate 60.9%) and the sitting group (HR 19.91%, and lactate 23.4%). So the results of this study provide evidence that post-match cycling can contribute to a more effective active recovery strategy. Thus the results of this study can be used as a reference for coaches and athletes in a good recovery process after a football match.